Legitimate, ¿Pars hereditatis o pars bonorum? - Aguilar Llanos, Benjamín (2017)
This paper is about the legitimate as an institution of the Inheritance Law and it focus in the discussion over if it would be considered as a pars hereditatis or as a pars bonorum. Following that, the author links the legitimate with the family institution along with how it could be a correspondence between who can receive this inheritance anticipated and who could receive the inheritance. Likewise, backed on national legislation the author takes a stand saying that the legitimate is pars hereditatis because of includes the heirs only. Finally, the author give us more scopes regarding the legitimate while explains how it be related with the institution of collation.